Kualitas Kinerja Layanan Nasabah PT Bank Jateng - Mursid, Ali; Suhartono, Entot; Suhana, Suhana (PRESTASI, 2012)
Customer satisfaction isÂ  keywords for a company running in service to achieve its competitive advantage. A bank as one of service companies is also insisted to improve the quality of service to win the tight competition nowday. PT Bank Jateng, a bank belonging to central java province has tried to do its best in serving the customers. Many have been done to improve the service quality to the customers. Based on the mystery shopper done, there are still many weaknessess in many sides of services to be improved. They are in customer service, teller, ATM and restroom services. Many suggestions are as follows: quick and easy procedure of service, quick and thorough customer acceptance, responsive in handling customersâs complaints, always ready to serve at any time, knowledge and capability of staffs, the numbers of seats provided, cleaning restroom dan other facilities and entertainment and information media in waiting room.Keywords: customer satisfaction, competitive advantage, mystery shopperCustomer satisfaction isÂ  keywords for a company running in service to achieve its competitive advantage. A bank as one of service companies is also insisted to improve the quality of service to win the tight competition nowday. PT Bank Jateng, a bank belonging to central java province has tried to do its best in serving the customers. Many have been done to improve the service quality to the customers. Based on the mystery shopper done, there are still many weaknessess in many sides of services to be improved. They are in customer service, teller, ATM and restroom services. Many suggestions are as follows: quick and easy procedure of service, quick and thorough customer acceptance, responsive in handling customersâs complaints, always ready to serve at any time, knowledge and capability of staffs, the numbers of seats provided, cleaning restroom dan other facilities and entertainment and information media in waiting room.Keywords: customer satisfaction, competitive advantage, mystery shopper